Report writing for criminal justice professionals - Miller, Larry, 1953 August 26-; Whitehead, John T. (Amsterdam ; Boston : Anderson Pub., 2011)
Synopsis: So much of the process of criminal justice depends on good documentation, and criminal justice professionals can spend as much as 50-75% of their time writing up administrative and research reports. Much of the legal process depends on the careful documentation that records crucial information. And yet most of these law enforcement, security, corrections, and probation and parole officers have not had adequate training in how to provide a well-written, accurate, brief, and complete report. Report Writing for Criminal Justice Professionals provides practical advice on report writing -- with specific writing samples and guidelines. The authors go beyond the routine English grammar approach to deal with the difficult but often-ignored problem of documentation that will hold up in court. Important concepts are emphasized with related checklists, forms, and pull-out chapter tests. The material is organized into three sections: The Nature of Report Writing, The Mechanics of Report Writing, and The Modernization of Report Writing. New To This Edition Updated and revised with new material on forensics and scientific reports, crime reporting, common errors in forensic reports, and automation of report writing. Appendixes are thoroughly revised, with new examples of reporting forms, worksheets, and reports, including a sample forensic lab report and presentence investigation report.
The why and how of report writing -- Starting to write -- The face page -- The narrative. the continuation page and follow-up report -- Habits that make for speedy writing -- Other types of writing -- Reading and correcting reports -- Simplified study of grammar -- Avoiding errors in sentence structure -- Making punctuation work -- Breaking the spelling jinx -- Using or abusing words -- Abbreviating and capitalizing -- Innovations and predictions in criminal justice.
Includes index.
Includes bibliographical references and index.
Keywords: Police reports -- Authorship; English language -- Rhetoric; Report writing; English language -- Rhetoric; Police reports -- Authorship; Report writing